1996
DOI: 10.1177/0002764296039004009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Public Support for Electronic House Arrest

Abstract: This article builds upon an earlier effort to examine citizens' overall support for electronic house arrest (EHA). It explores a variety of demographic and attitudinal factors measured in a survey of residents in Oneida County, New York, and identifies predictors of support for EHA when used with “minor” and “serious” offenders. Survey findings indicate that those who favor the use of EHA with minor offenders have limited faith in the ability of incarceration to reduce crime and view EHA as a cost-effective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Some studies have found younger respondents to be more punitive (Borg 1997;Grasmick and McGill 1994), while other studies depict older respondents as more punitive (Elrod and Brown 1996;Jan, Ball, and Walsh 2008;Young and Thompson 1995). These divergent findings are often contextualized by the specific issue under examination (e.g., rape, the death penalty, juvenile crime, etc.).…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…Some studies have found younger respondents to be more punitive (Borg 1997;Grasmick and McGill 1994), while other studies depict older respondents as more punitive (Elrod and Brown 1996;Jan, Ball, and Walsh 2008;Young and Thompson 1995). These divergent findings are often contextualized by the specific issue under examination (e.g., rape, the death penalty, juvenile crime, etc.).…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…Shifts in correctional policy and practice like the end of the industrial, for-profit prison during the Great Depression, the discontinuation of Pell grants for prisoners in the 1990s, and the increase in punitive punishments as part of "get tough" policy were influenced, at least in part, by changing public sentiments (Garland, 2002;Seiter, 2010). Considering the current economic environment, identifying specific areas of community support and opposition can be very beneficial for gaining important political leverage (Elrod & Brown, 1996). Furthermore, the modern reentry movement is founded on the belief that at the most fundamental level prisoner reentry is a community issue, which necessitates a collaborative response among correctional organizations and the communities to which inmates return Travis, Solomon, & Waul, 2001).…”
mentioning
confidence: 99%
“…Understanding public views on reentry programs is an important step toward developing strong and lasting collaborations in the community. In addition, by knowing the nuances of public sentiment toward correctional proposals, information strategies can be undertaken to clarify misunderstandings and potentially overcome resistance (Elrod & Brown, 1996).…”
mentioning
confidence: 99%
“…Because of its focus on surveillance, it has not been as heavily criticized as being "soft on crime" and a threat to public safety as have other community sentencing options. Thus, EM has been viewed as having a deterrent effect because it enables the offender to be more closely monitored than do other alternatives to incarceration (Elrod & Brown, 1996;Hofer & Meierhoefer, 1987;Palumbo et al 1992;Tonry, 1998a).…”
Section: Electronic Monitoringmentioning
confidence: 99%
“…Given the penal harm movement (Clear, 1994) and conservative ideological influences on correctional policies across the United States (Elrod & Brown, 1996), the State Board of Pardons and Paroles (2000) instituted a policy in July 1995 that all offenders serving time for violent offenses who are paroled from Georgia prisons be placed on maximum supervision with electronic monitoring (EM) for a minimum of three months. It was believed that such a policy would provide greater community safety because offenders would be more closely monitored than they would be with standard parole supervision alone.…”
mentioning
confidence: 99%